IS THE INCIDENCE OF LOW BIRTH WEIGHT IN INDONESIA DUE TO PREECLAMPSIA DURING PREGNANCY?: A META-ANALYSIS - Simbolon, Demsa; Ningsih, Lisma; Andriani, Lusi; Kamsiah (Universitas Airlangga, 2025)
Preeclampsia (PE) is a pregnancy disorder characterized by hypertension, edema, and proteinuria. Preeclampsia remains one of the main causes of maternal death in Indonesia. Preeclampsia can cause stunting of fetal growth because of unbalanced nutrition. Preeclampsia can result in insufficient blood flow to the placenta, reducing the intake of nutrients and oxygen by the fetus, which affects its weight. The long-term impact is that infants may have low birth weights (LBW). This study aimed to determine the estimated combined effect of preeclampsia in pregnant women and the incidence of LBW. This study used a meta-analysis method to analyze articles from Google Scholar using the following criteria: published between 2012 and 2024, full-text availability, case-control or cross-sectional studies, multivariate analysis, and reported odds ratios (OR). Articles were collected using the PRISMA diagram and analyzed using Review Manager 5.4 application with a random-effects analysis model. This study analyzed 36 cross-sectional results (OR 95% CI: 2.16; 1.51–3.08) and 22 case-control results (OR 95% CI: 3.15; 1.76–5.64), showing a significant association between preeclampsia in pregnant women and the incidence of low birth weight in infants (p-value < 0.00001, which is < 0.05). Pregnant women with high levels of preeclampsia were at a higher risk of giving birth to infants with low birth weight (odds ratio [OR 95% CI: 4.66; 1.76–12.31, p-value < 0.00001).